PROTECTIVE AND DOSE-DEPENDENT EFFECTS OF Cucumis melo SEED OIL ON TESTICULAR FUNCTION AND OXIDATIVE STRESS IN TRICARBALLYLIC ACID – INDUCED TOXICITY IN MALE WISTAR RATS - Enyioma-Alozie, Swesme (FUDMA Journal of Sciences, 2025)
Cucumis melo seed oil (CMSO), rich in polyunsaturated fatty acids, tocopherols, and phenolic antioxidants, has demonstrated antioxidant and anti-inflammatory potential. This study evaluated the dose-dependent protective effects of CMSO on Tricarballylic acid (TCA)-induced testicular oxidative stress and functional impairment in male Wistar rats. Twenty-five male Wistar rats were randomly assigned into five groups (n = 5) and treated orally for 21 days: Control (normal saline), TCA only (200 mg/kg), and TCA (200 mg/kg) co-administered with CMSO at 100, 200, and 300 mg/kg. Body weight, oxidative stress markers (SOD, MDA), reproductive hormones (FSH, testosterone), sperm parameters, and testicular histology were assessed. TCA significantly decreased SOD activity (10.42±1.61 U/mg; p
Keywords: Cucumis melo seed oil; Tricarballylic acid; Testicular toxicity; Oxidative stress; Sperm quality; Wistar rats